Analysis of Spelling Errors in Student Thesis Health Study Programs - Juliana (PT Inovasi Pratama Internasional, 2022)
The purpose of this study is to describe errors in the use of capital letters, use of punctuation marks, and writing words in health study program student thesis. The sample of this study is 4 student thesis in 2022. Data collection is carried out using reading and note-taking techniques, while The data collection instrument uses a human instrument, namely the researcher himself. The data analysis technique used is a qualitative descriptive analysis technique. The validity of the data was obtained by means of interrater and interrater . The results of this study indicate that there are 248 spelling errors in the student thesis of the Health Study Program at Universitas Aufa Royhan, consisting of (1) 9 errors in the use of capital letters. (2) Errors in writing prepositions in and to as many as 30 errors which include errors in writing prepositions in as many as 27 errors, errors in writing prepositions to as many as 3 errors, while the affixes in -, to and prepositions from are not found errors in student thesis. (3) 208 mistakes in using punctuation, including 33 mistakes in using dot (.) punctuation, 164 mistakes in using comma (,) punctuation, 1 mistake in using dash (-), 1 mistake in using question mark (?) as many as 4 errors, and errors in the use of colon punctuation (:) as many as 8 errors.